1993
DOI: 10.1111/j.1365-2125.1993.tb05690.x
|View full text |Cite
|
Sign up to set email alerts
|

Equipotent inhibition by R(−)−, S(+)‐ and racemic ibuprofen of human polymorphonuclear cell function in vitro.

Abstract: 1. The effects of racemic (rac) ibuprofen and its S(+)‐ and R(−)− enantiomers on functions of human polymorphonuclear cells (PMN) and platelets were studied in vitro. 2. Rac‐ibuprofen inhibited PMN functions (O2‐ generation, beta‐glucuronidase release, LTB4 formation). Similar IC50 values (40‐100 microM) were obtained for the S(+)‐ and R(‐ )‐enantiomers. 3. All forms of ibuprofen inhibited cyclooxygenase‐ related platelet functions (aggregation, thromboxane formation). The S(+)‐enantiomer was about twice as ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Therefore, significant increases of MPO activity caused by racemic (50 mg/kg) and R (-)-ketoprofen (25 mg/kg) treatments (Table 2) can not be attributed to S(+)-enatiomer initially present or produced from inversion. Although leukocyte accumulation is necessary but not sufficient to induce ulcer formation, our results confirm that the R (-)-enantiomers of arylpropionic acid derivatives can contribute to modifications in PMN functions [13,15,16] related with the fact that the combination of R (-)-and S(+)-enantiomers results in a significant increase in ulcer formation compared with that produced by the pure S(+)-enantiomer [13].…”
Section: Table 2 Activities Of Superoxide Dismutase (Sod) Xanthine supporting
confidence: 51%
“…Therefore, significant increases of MPO activity caused by racemic (50 mg/kg) and R (-)-ketoprofen (25 mg/kg) treatments (Table 2) can not be attributed to S(+)-enatiomer initially present or produced from inversion. Although leukocyte accumulation is necessary but not sufficient to induce ulcer formation, our results confirm that the R (-)-enantiomers of arylpropionic acid derivatives can contribute to modifications in PMN functions [13,15,16] related with the fact that the combination of R (-)-and S(+)-enantiomers results in a significant increase in ulcer formation compared with that produced by the pure S(+)-enantiomer [13].…”
Section: Table 2 Activities Of Superoxide Dismutase (Sod) Xanthine supporting
confidence: 51%
“…It is usually considered that the pharmacodynamic properties of ibuprofen reside almost exclusively in the (S)-enantiomer [4]. The latter was reported to be about 160 times more potent than (R)-ibuprofen in inhibiting prostaglandin synthesis in vitro [4] but there are conflicting data [5].…”
Section: Introductionmentioning
confidence: 99%
“…4 It has also been suggested that (R)-ibuprofen may reduce renal function in isolated perfused rat kidney 5 and may cause changes in polymorphonuclear lymphocyte function. 6 The R enantiomer of etodolac, a non-2-arylpropionate NSAID which undergoes no chiral inversion, has been previously demonstrated to induce some degree of intestinal permeability changes in the rat. 7 Thus, the R enantiomers of these drugs may not be as inactive as once thought.…”
mentioning
confidence: 99%